Arthropod pests and their management, natural enemies and flora visitors associated with castor (Ricinus communis), a biofuel plant: a review. (2020)
Interest in bioenergetic crops, such as the castor oil plant Ricinus communis (Euphorbiaceae), for production of biodiesel has increased in recent years. In this paper, phytophagous arthropods, their natural enemies and floral visitors associated with this plant in the world are reviewed. Despite its insecticidal properties, arthropods have been reported feeding on R. communis plants. The arthropod pests of R. communis damage all parts of the plant, including the seeds, where some toxic compounds are even more concentrated. In the scientific databases, we found reports of 193 arthropods associated to R. communis in different parts of the world. This information obtained in the scientific databases was concentrated in a database and analyzed according to the coevolutive hypothesis, which allows us to predict that the greatest wealth and abundance of phytogenic arthropods is found in the center of origin by R. communis. According to this review, Achaea janata, Spodoptera litura, Edwardsiana flavescens, Liriomyza trifolii, L. sativae, Spilosoma obliqua, Cogenethes punctiferalis, Oxyrhachis taranda, and Helicoverpa armigera are the most devastating pests in Asia. In Africa, Agrotis ipsilon, S. exigua, Nezara viridula, Trialeurodes ricini, and Tetranychus urticae were mentioned as the most important. In Central and South-America, Phyllophaga sp., Agrietes sp., Erinnyis ello, N. viridula, Corythucha gossypii, Falconia antioquiana, and S. marima are reported as pests of economic importance. The most commonly reported natural enemies of some of these arthropod pests were species of Bacillus thuringiensis, B. cereus, B. popilliae, Trichogramma achaeae, T. chilonis, T. minutum, T. australicum, T. dendrolimi, T. pretiosum, T. evanescens, Microplitis rufiventris, M. maculipennis, M. ophiusae, Telenomus remus, T. proditor, Stethorus siphonulus and S. histrio. Apis mellifera is recorded as the main insect pollinator of R. communis. Pest management methods used against the arthropod pests of R. communis include biological, ethological, mechanical, cultural, genetic, and chemical control.